Darurat Lunturnya Nilai Pancasila pada Generasi Digital melalui Transformasi Pendidikan Karakter di SMP - Siti Zainia Miftahul Jannah; Moh. Thohir; Mujahidah Fitria (Jurnal Cendekia Pendidikan, 2026)
The phenomenon of declining internalization of Pancasila values ​​among students reveals a gap between their cognitive knowledge and the practical application of these values ​​in daily life. This study aims to explore the perceptions of students at SMP Ummul Quro regarding Pancasila values, analyze how these values ​​are internalized and applied within school, family, and community environments, and identify the influencing factors. A qualitative approach utilizing a phenomenological study design was employed, allowing for an in-depth exploration of the students' subjective experiences. Data were collected through observation, in-depth interviews, and documentation, involving ten informants: six students from various grade levels, as well as Civics (PPKn) teachers and homeroom teachers (Grades VII, VIII, and IX). The findings indicate that while students possess a solid cognitive understanding of the five principles of Pancasila, the internalization and implementation of these values ​​remain uneven. Values ​​such as mutual cooperation (*gotong royong*), discipline, responsibility, deliberation (*musyawarah*), and tolerance are beginning to manifest in daily activities, although their consistency is influenced by various factors. External factors include the roles of teachers, parents, peers, and school culture, while internal factors encompass the students' own awareness and personal motivation. The study concludes that although Pancasila values ​​are formally taught, deeper internalization requires synergy among the school, family, and community—facilitated by contextual learning strategies and sustained habituation—to ensure that a character embodying Pancasila truly takes root in the students.